2022
DOI: 10.3389/fpls.2022.1023178
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of cucumber resistance under salt stress by 2, 4-epibrassinolide lactones

Abstract: This study investigated the effects of exogenous 2, 4-epibrassinolide lactone (EBR) on the growth, photosynthetic pigments, antioxidant defense system, ion homeostasis, MAPK cascade and key genes of SOS signaling pathway of cucumber seedlings under salt stress using cucumber “Xinchun 4” as the test material. The experiment was set up with four treatments: foliar spraying of distilled water (CK), 50 mmol.L-1 NaCl (NaCl), 50 mmol.L-1 NaCl+foliar spray of 0.02 μmol.L-1 EBR (EBR+NaCl), and 50 mmol.L-1 NaCl+foliar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Following herbivore damage and/or external application, MJ activates direct (defense proteins) and indirect (volatile emissions) defense mechanisms 33,[65][66][67] by activating the antioxidant system, the accumulation of defense chemicals and attracting natural enemies. 68 Jasmonic acids and their derivatives have been shown to regulate gene expression in plant defense responses. [69][70][71][72][73] Jasmonatetreated plants usually defend against herbivores and diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following herbivore damage and/or external application, MJ activates direct (defense proteins) and indirect (volatile emissions) defense mechanisms 33,[65][66][67] by activating the antioxidant system, the accumulation of defense chemicals and attracting natural enemies. 68 Jasmonic acids and their derivatives have been shown to regulate gene expression in plant defense responses. [69][70][71][72][73] Jasmonatetreated plants usually defend against herbivores and diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Herbivores are considered a biotic stress to plants and different defense signaling pathways can be activated in an infested plant. Following herbivore damage and/or external application, MJ activates direct (defense proteins) and indirect (volatile emissions) defense mechanisms 33,65–67 by activating the antioxidant system, the accumulation of defense chemicals and attracting natural enemies 68 …”
Section: Discussionmentioning
confidence: 99%
“…The soluble sugar contents in the leaves of collected seedlings were measured according to the published literature [68]. Briefly, fresh leaves (0.1 g) were ground in a mortar containing 5 mL of 80% ethanol solution, and the grinding fluid was moved into a 10 mL centrifuge tube in an 85 • C water bath for 30 min.…”
Section: Soluble Sugar and Protein Content Determinationmentioning
confidence: 99%
“…In plants, the content of redox substances is strictly regulated. In addition, it has been reported that the rate of photosynthetic activity has been significantly improved (He et al, 2022). In terms of fruit quality improvement, BR spraying at appropriate mass concentrations was able to increase the yield of sugar beet tubers but had no significant effect on total sugar content (Lv et al, 2019).…”
Section: Introductionmentioning
confidence: 99%